2006
DOI: 10.1016/j.jhsb.2006.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Pain Phenomena and Sensory Recovery following Brachial Plexus Avulsion Injury and Surgical Repairs

Abstract: Seventy-six patients with severe brachial plexus avulsion injuries were studied using pain questionnaires and quantitative sensory testing. There was significant correlation between pain intensity and the number of roots avulsed prior to surgery (P=0.0004) and surgical repairs were associated with pain relief. Sensory recovery to thermal stimuli was observed, mainly in the C5 dermatome. Allodynia to mechanical and thermal stimuli was observed in the border zone of affected and unaffected dermatomes in 18% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
1
4

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 65 publications
5
78
1
4
Order By: Relevance
“…Choi et al reported that patients who had undergone brachial plexus reconstruction had a moderately high quality of life and that 75% had substantial pain 52 . In a study of patients with a brachial plexus avulsion injury, Htut et al found the greatest pain to be in patients who had not had reconstructive surgery 5 . Kato et al reported positive correlations between pain intensity and the number of nerve root avulsions and a longer interval between the injury and surgery 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al reported that patients who had undergone brachial plexus reconstruction had a moderately high quality of life and that 75% had substantial pain 52 . In a study of patients with a brachial plexus avulsion injury, Htut et al found the greatest pain to be in patients who had not had reconstructive surgery 5 . Kato et al reported positive correlations between pain intensity and the number of nerve root avulsions and a longer interval between the injury and surgery 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of outcomes following upper-extremity peripheral nerve injury frequently include assessment of physical impairment [1][2][3][4][5][6][7][8][9][10][11][12] . Evaluations of the impact of the physical impairment on the patient and validated measures of disability are not commonly included in the surgical literature.…”
mentioning
confidence: 99%
“…Pain following traumatic nerve injuries has been reported to be associated with poor outcomes 5,15,[59][60][61] . Brachial plexus injury is often associated with more severe pain and is a significant predictor of disability.…”
Section: Discussionmentioning
confidence: 99%
“…In the surgeons' general comments submitted in the survey, "chronic neuropathic pain" was often attributed to neuropathic pain, which was uncontrolled and nonresponsive to treatment. Neuropathic pain and cold sensitivity are frequently reported as contributing to poor outcome following nerve injury [6,12,19,20,25,[27][28][29]32]. However, few outcome studies provide details regarding these patient symptoms, and most studies of nerve injured patients report only motor and sensory function.…”
Section: Discussionmentioning
confidence: 99%
“…Many outcome studies of nerve-injured patients present motor and sensory functional outcomes but do not report information regarding the absence or presence of pain [1,7,16,17,30,35,36,38,41,44]. In the surgical literature, many studies that report pain in nerve-injured patients generally use unidimensional measures (verbal ratings or visual analog scales of pain intensity) and do not include assessment of the psychosocial factors that may be associated with pain [5,8,28,32,34,40,42].…”
Section: Introductionmentioning
confidence: 99%